«Democracy» or «Autocracy»: How to Escape the Grey Zone of Hybridity - Ратушний, Денис Миколайович (Київський національний університет імені Тараса Шевченка, 2024)
The article is devoted to the current approaches to the study of hybrid regimes, the history of this concept and the problems that arise in connection with the theory of hybrid regimes. The author analyses how the third wave of democratisation has led to the emergence of a «grey zone» between democracies and dictatorships, which in turn has led to the emergence of the theory of hybrid regimes. It is determined that the central issue in the study of hybrid regimes is the notion of democracy and autocracy. The author analyses how the concept of democracy has changed from the minimalist procedural approach of Joseph Schumpeter to the polyarchy of Robert Dahl. Two main approaches to understanding ‘hybridity’ are considered: as the interpenetration of authoritarian and democratic components, and as the superiority of informal rules over formal ones. It is found that the main problem with theories of hybrid regimes is that they focus either on ‘imperfect democracies’ or ‘soft dictatorships’, which leads to an internal contradiction: the theory of hybrid regimes lacks a holistic analysis of hybridity. The author describes how this problem is being addressed by contemporary researchers. The emphasis is placed on Matthijs Bogaards «double-rooted strategy» with a parallel analysis of democracies and autocracies, and Yuri Matsiyevsky’s analysis of the relationship between formal and informal rules. As a result of the study, it is proposed to use the concept of a ‘hybrid regime’ as a starting point for the research, which should prevent bias towards the study of democracies or autocracies. However, the ultimate goal of studying specific political regimes should be their qualification them using dichotomous approach.

Стаття присвячена актуальним підходам вивчення гібридних режимів, історії цього поняття та проблемам, які виникають у зв’язку з теорією гібридних режимів. Аналізується, як третя хвиля демократизації призвела до появи «сірої зони» між демократіями та диктатурами, що своєю чергою спонукало до появи теорії гібридних режимів. Обґрунтовано, що центральним питанням у дослідженнях гібридних режимів є поняття демократії і автократії. Проаналізовано, як змінювалася концепція демократії від мінімалістичного процедурного підходу Йозефа Шумпетера до багатоскладового розуміння демократії. Розглянуто два головні підходи до розуміння «гібридності»: як взаємопроникнення авторитарних і демократичних складових і як переваги неформальних правил над формальними. З’ясовано, що головною проблемою теорій гібридного режиму є зосередження уваги або на «недосконалих демократіях», або на «м’яких диктатурах», унаслідок чого виникає внутрішня суперечність: теоріям гібридного режиму бракує цілісного аналізу гібридності. Описано, як цю проблему вирішують сучасні дослідники. Акцент зроблено на «подвійній стратегії» Матеуса Богардса з паралельним аналізом демократій і автократій, та аналізі співвідношення формальних і неформальних правил у Юрія Мацієвського. У результаті дослідження запропоновано використовувати концепцію «гібридного режиму» як вихідну точку дослідження, що має запобігти заангажованості у бік вивчення демократій чи автократій. Утім, остаточною метою вивчення конкретних політичних режимів має бути їх кваліфікація за допомогою дихотомічного підходу.
«Демократія» чи «автократія»: як вийти із сірої зони гібридності
Keywords: hybrid regime; democracy; autocracy; political regime; «grey zone»; гібридний режим; демократія; автократія; політичний режим; «сіра зона»